Participação do hipocampo reptiliano nos processos de memória : um estudo eletrofisiológico - Santos, Heitor Franco (2021)
Introduction: Memory corresponds to the ability to retrieve information that has been stored. Among the various techniques, electrophysiological memory studies allow us to associate patterns of electrical responses and have gained strength, especially in mammals. Studies on memory in lizards have pointed to possible homologies between cortical areas of the reptilian brain and the hippocampus in mammals, an area involved with memory processing. However, some gaps on the preservation of the functionality of these cortical areas, in less derived groups, have not been answered through molecular and morphological analyzes. In this sense, the objective of the present study was to characterize the pattern of electrophysiological activity of the dorsal cortex (DC) of the tropical lizard Tropidurus hispidus in the processes of aversive memory. Methodology: 10 lizards were used, divided into two groups: control (G.CTRL) and experimental (G.EXPT). Animals from both groups were submitted to stereotactic surgery to implant electrodes of superficial contact with the cortex. The experimental protocol was developed in two consecutive days. On day 1 (training), lizards from both groups, first G.CTRL and then G.EXPT, were used to the task space individually, for 10 min. After that time, the ambience started, followed by an electric record of the CD, for 10 min. The G.CTRL animals continue to be exposed and were exposed to an empty cage. After G.CTRL, G.EXPT was set for 10 minutes and recorded simultaneously. Followed by exposure to a cage containing a domestic cat, aversive model. During the 10 min exposure, the electrophysiological signal was recorded simultaneously. On day 2 (test), 24h after training, the lizards of both groups were used individually, for 10 min, in the same terrarium on day 1 and after that time, the animals G.CTRL and G.EXPT went through the setting, for 10 min, and subsequent exposure to an empty cage. Simultaneous electrophysiological recording was performed during the setting and exposure to the cage. The recorded electrical signal was evaluated for its normal distribution, it was randomly selected for characterization, the predominant characteristics of temporal development were measured, followed by the fragmented distribution in frequency bands using the Welch method and the interaction between frequencies was evaluated by cross-frequency coupling. Thus, a profile of participation and interaction between behavioral conditions (neutral and aversive) was evaluated. Finally analyzed statistically. Result and Discussion: Signal analyzes showed that the pattern of electrophysiological occurrence is dominant at low frequencies of 1-3 Hz, with high amplitudes, and decreases its amplitude for frequencies above 4 Hz. The spectrum, in domain bands, is similar to what is found in mammals: band 01 (1-5 Hz) band 02 (6-10 Hz) band 03 (11-17 Hz) and band 04 (18-23 Hz), which can categorize the electrophysiological domain of memory aversive. G.EXPT, in training and testing, showed electrophysiological changes sustained by exposure to the cat. The signal amplitude of G.EXPT is greater when compared to the ambient condition and to the G.CTRL. When analyzing the effect of exposure for band 01 to band 04: p <0.05, the aversive stimulus was able to change the electrophysiological profile with greater effect when compared to the neutral stimulus. This training response is repeated in the test, with the electrical activity changed for band 04: p <0.05, which may represent a possible participation of the DC area with tasks associated with memory. Amplitude increases in frequencies above 20 Hz can be expressed as frequency coupling between phase-amplitude. This interaction was observed with the regions of interest (ROI): in delta (2-4 Hz) and theta (4-8 Hz) with high frequencies (20-80 Hz) and an increased response was observed for G.EXPT in the ROI coupling: 4-8 (phase) and 20-80 (amplitude) training: p <0.05 and in the test p <0.05. This response is well related to the plastic processes resulting from the stimulation and formation of memory. Conclusion: The observed electrophysiological wave patterns in the DC are associated with modulation in the mode of synaptic communication, which regulate mnemonic functions during an aversive task.